Adjuvant Hyperbaric Oxigen and ozone therapy in the treatment of chonic leg and foot ulcers (pilot clinical study) (Ozone Therapy Global Journal, 2011)
This pilot study describes the clinical effects of Adjunctive Hyperbaric Oxygen Therapy(HBOT) and Ozone Therapy in the treatment of chronic ulcers most of which did notrespond to standard wound care and conventional methods of therapy and the patientswere threatened by amputation. HBO and Ozone Therapy increased the healing rateof these ulcers, and avoided amputation. Adjuvant HBO and Ozone Therapy showedeffectiv e adjun ctive the rapy and we re commend a Randomized Controlle d Trial toprove that effect.